A de novo frameshift mutation in chromodomain helicase DNA‐binding domain 8 (CHD8): A case report and literature review. Issue 5 (20th January 2016) - Merner, Nancy; Forgeot d'Arc, Baudouin; Bell, Scott C.; Maussion, Gilles; Peng, Huashan; Gauthier, Julie; Crapper, Liam; Hamdan, Fadi F.; Michaud, Jacques L.; Mottron, Laurent; Rouleau, Guy A.; Ernst, Carl
Abstract : Mutations in chromodomain helicase DNA‐binding domain 8 ( CHD8 ) have been identified in independent genotyping studies of autism spectrum disorder. To better understand the phenotype associated with CHD8 mutations, we genotyped all CHD8 exons in carefully assessed cohorts of autism (n = 142), schizophrenia (SCZ; n = 143), and intellectual disability (ID; n = 94). We identified one frameshift mutation, seven non‐synonymous variants, and six synonymous variants. The frameshift mutation, p.Asn2092Lysfs*2, which creates a premature stop codon leading to the loss of 212 amino acids of the protein, was from an autism case on whom we present multiple clinical assessments and pharmacological treatments spanning more than 10 years. RNA and protein analysis support a model where the transcript generated from the mutant allele results in haploinsufficiency of CHD8 . This case report supports the association of CHD8 mutations with classical autism, macrocephaly, infantile hypotonia, speech delay, lack of major ID, and psychopathology in late adolescence caused by insufficient dosage of CHD8 . Review of 16 other CHD8 mutation cases suggests that clinical features and their severity vary considerably across individuals; however, these data support a CHD8 mutation syndrome, further highlighting the importance of genomic medicine to guide clinical assessment and treatment. © 2016 Wiley Periodicals, Inc.